PENINGKATAN HASIL BELAJAR BIOLOGI KELAS IX SMP ITTIHAD MAKASSAR MELALUI MODEL PEMBELAJARAN QUANTUM TEACHING DENGAN METODE PRAKTIKUM - Putri Athirah Azis; A Bida Purnamasari (Universitas Cokroaminoto Palopo, 2022)
The study aims was to improve the biology learning outcomes of Class IX students of SMP Ittihad Makassar through the application of the Quantum Teaching model to Class IX students of SMP Ittihad Makassar with the practical method. This type of research is classroom action research with data collection techniques through tests and observations. Observational data were analyzed qualitatively in the form of a description of student learning activities, and then analyzed quantitatively in the form of averages and categorization of student learning outcomes. The subjects in this study were all 20 students of class IX SMP Ittihad Makassar. The results of this study indicate an increase in biology learning outcomes for class IX students of SMP Ittihad Makassar through the application of the Quantum Teaching model with the practicum method. This can be seen from the results of student learning tests which show an increase from cycle I to cycle II with an average of 63.00% increasing to 82.00%.